The new Christians : dispatches from the emergent frontier - Jones, Tony, 1968- (San Francisco, CA : Jossey-Bass, 2008)
Explores the beliefs, practices, and faith of emergent Christians around the country, discussing the origins, theology, interpretation of Scripture, and sense of community promoted by the emerging church movement.
A living way : emergent visions series foreword -- Introduction: What is emergent? -- Leaving the old country -- Church is dead? -- Signs of death and life -- The problem on the left -- A case study : go where I send thee -- The problem on the right -- A case study : don't ask us about the chickens -- The real problem : left versus right -- Caught in the crossfire --- Dispatch from the blogosphere : musings of a postmodern Negro -- Dispatches from the frontier of the American church -- An allegory -- An alternative ending -- Geological musings -- What exactly is emerging? -- The beginnings -- The Bible is propaganda? -- The new kind of Christian effect -- Meanwhile, across the pond -- Then till now -- The church's choice -- Dispatch from the Rocky Mountains : Katie and Kristen -- Who are the emergent Christians? -- Hunches and intuitions -- Influencing culture or influenced by culture -- An envelope of friendship -- An emergent voters' guide -- Dispatch from I-35 : the terrific tale of Trucker Frank -- The theology, stupid -- Dartmouth days -- What, exactly, is theology? -- Theology on the rise -- Going deep -- Skiing the slippery slope -- So, a biblicist and a relativist walk into a pastor's conference -- The expurgated lectionary -- Dispatch from seminary : legalisms of the left -- After objectivity, beautiful truth -- The thrill of interpretation -- Reading the whole Bible -- Sonny, it ain't nothing till I call it? -- Truth (a.k.a. God) -- After objectivity : dialogue -- Beautiful, messy, incarnational truth -- Paradoxes -- Dispatch from the end of a three-mile dirt road : recovering church -- Inside the emergent church -- It's a great day at Jacob's well! -- Wikichurch -- Tightly knit : journey -- Binitarians -- The people's liturgy : Church of the Apostles -- Time to rethink seminary -- My church : a paean to Solomon's porch -- Epilogue: Feral Christians.
Includes bibliographical references and index.
Keywords: Christianity -- 21st century; Emerging church movement; Postmodernism -- Religious aspects -- Christianity